The Use of Wayang for Sociology Learning in Conflict and Integration Materials - Prihanto, P; Octaviani, Saly Kurnia (International Islamic Schools Alliance, 2024)
Conflict and integration materials are part of sociology topics that relatively abstract and not attractive leading to low motivation for students to learn. Material in sociology will be easily conveyed by teachers and accepted by students when using media. Learning conflict and integration material raises many issues in stories in society. Wayang is a traditional performance that tells a lot about real conditions in society and functions as not only learning medium in sociology, especially material on conflict and integration but also preserving culture of wayang for generation Z. This research aims to provide references for teachers in using learning media. This research uses a qualitative descriptive method that focuses on the natural conditions of the experiment or data sources so that researchers obtain valid and in-depth information that is appropriate to the conditions of the research field. The main data for this research were obtained from participant observation of the teaching and learning process in the classroom. There are 3 results of this research. Firstly, learning the sociology of conflict and integration material using Wayang becomes more enjoyable and easier to understand for Al-Firdaus High School students. Secondly, the implementation of learning using Wayang related to reality in society through wayang stories and its plots motivated Al Firdaus High School students to study. Thirdly, the use of wayang as a sociology lesson provides a new reference in the learning process which is increasingly varied to be used as a learning medium and can be applied in other subjects.